PERLINDUNGAN HUKUM TERHADAP KREDITOR SEPARATIS DALAM EKSEKUSI HARTA BOEDEL PAILIT APABILA DIHADAPKAN DENGAN SITA PERKARA TINDAK PIDANA KORUPSI - Mubarak, Hakim Harismawan; Kharisma, Dona Budi (Fakultas Hukum Universitas Sebelas Maret, 2023)
This article aims to explain the legal position of the state in the confiscation of a criminal act of corruption that is faced with confiscation in bankruptcy, position, and legal protection for separatist creditors in the execution of bankruptcy assets when confronted with confiscation in a criminal act of corruption. The research method used is normative legal research with a statutory approach and a case approach. Based on the results of the research, it can be concluded that the position of creditors is weak in the sense that they do not have legal certainty when the execution of the bankruptcy assets is faced with seizure in a corruption case, so that no party can execute the bankruptcy property which is included in the confiscation in the case of crime. criminal corruption until there is a verdict with permanent legal force, and the loss to the state has been paid off based on the sale of assets included in the assets obtained from the proceeds of the criminal act of corruption as stipulated in the court decision. In the confiscation of a corruption crime case, the principle of public interest applies so that the position of the confiscation in the corruption case is stronger than the seizure contained in the execution of the bankruptcy bailout which in fact is the application of the principle of personal interest. This has resulted in a stronger public interest principle as emphasized in the Preamble to the 1945 Constitution of the Republic of Indonesia (vide paragraph IV) along with its torso in Articles 33 and 44 have outlined that all government officials must carry out activities leading to the implementation. public interest.